2017
DOI: 10.1016/j.anbehav.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping and cue denial in avian acoustic signals

Abstract: Although some signals seem adapted to maximize transmission of cues to intended receivers, others appear to have been selected to deny specific types of cues to unwanted receivers. We review three categories of avian vocal signals that have been suggested to show adaptation for cue denial: aerial predator alarm calls, begging calls, and soft songs and calls. Evidence supports the conclusion that aerial alarm calls are adapted to deny localization cues and that begging calls and soft songs are adapted to deny d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Why do so many different species lower the amplitude of their songs during aggressive territorial interactions? One compelling explanation is the eavesdropping avoidance hypothesis (Dabelsteen et al, ), which proposes that individuals sing softly to avoid social eavesdropping by conspecific males or females, or interceptive eavesdropping by predators (McGregor, ; Searcy & Yasukawa, ). Eavesdroppers can impose high costs on signallers, in the case of both social eavesdropping (Mennill, Boag, & Ratcliffe, ) and interceptive eavesdropping (Randall & Matocq, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why do so many different species lower the amplitude of their songs during aggressive territorial interactions? One compelling explanation is the eavesdropping avoidance hypothesis (Dabelsteen et al, ), which proposes that individuals sing softly to avoid social eavesdropping by conspecific males or females, or interceptive eavesdropping by predators (McGregor, ; Searcy & Yasukawa, ). Eavesdroppers can impose high costs on signallers, in the case of both social eavesdropping (Mennill, Boag, & Ratcliffe, ) and interceptive eavesdropping (Randall & Matocq, ).…”
Section: Discussionmentioning
confidence: 99%
“…Why do so many different species lower the amplitude of their songs during aggressive territorial interactions? One compelling explanation is the eavesdropping avoidance hypothesis (Dabelsteen et al, 1998), which proposes that individuals sing softly to avoid social eavesdropping by conspecific males or females, or interceptive eavesdropping by predators (McGregor, 1993;Searcy & Yasukawa, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The latter type of soft songs tend to have the lowest amplitude and contain alternating sequences of low and high frequency elements covering a broader frequency range (1539-9118 Hz for warbled songs, 1762-8081 for crystallized soft songs and 2038-7999 Hz for broadcast songs, see Table 1 of Anderson et al 2008). Although usually assumed that the acoustic structure of soft song is selected for minimizing transmission distance (which would exacerbate the difficulty of their detection under urban noise), the evidence for this is as yet lacking for song sparrows (Akçay, Anderson, Nowicki, Beecher, & Searcy, 2015; Akçay & Beecher, 2012; Searcy & Yasukawa, 2017). In fact, a recent study found that soft songs (both crystallized and warbled) transmitted slightly better than broadcast songs when played at low amplitudes from a speaker and remeasured at different distances (Niederhauser, DuBois, Searcy, Nowicki, & Anderson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies involve the use of signal features that minimize cues available to eavesdroppers (i.e. cue denial; Searcy & Yasukawa, 2017), reflecting the intersection between responding to selection to avoid exploitation without overly compromising communication efficacy.…”
Section: (B) Reduction In Signal Ratementioning
confidence: 99%